Lexical Cohesion Used in “National Column” of the Jakarta Post - Sumani, Sumani; Kartikasari, Dyah (New Language Dimensions, 2022)
A newspaper has three main functions: informing, serving, and entertaining. From a linguistic point of view, especially discourse analysis, it is interesting to analyze how the news can relate to each other and how the news has unity from one element to another. The instrument to relate and unite from one element to another in discourse analysis is called cohesion. Cohesion is a meaningful relationship between two or more elements within the text. Meanwhile, there are two kinds of cohesion, they are grammatical cohesion and lexical cohesion. In this study, the researcher focuses on lexical cohesion. Lexical cohesion is a linguistic device that helps create unity in the text. It occurs when two or more elements in the text are related to their meaning. Besides, it is also viewed as one of the elements that help the reader quickly understand the writer's thoughts. This study mainly analyzes lexical cohesion's types and functions in the "National Column" of The Jakarta Post. The approach of this study is descriptive qualitative. The data sources of this study are "National Column" of The Jakarta Post which is issued from 26th to 30th March, 2012. The data were analyzed based on the theory of Halliday and Hasan's (1976), Taboada (2004), and Tanskanen (2006). This study shows that: (1) lexical cohesion is used in the "National Column" of The Jakarta Post. The types of lexical cohesion which are used are reiteration and collocation. Reiteration used in these columns consists of repetition, synonym, and superordinate. The sequence of lexical cohesion types used the most are collocation, repetition, superordinate, and synonym. (2) each type of lexical cohesion has a vital function. Reiteration is used to reiterate the previous item, either in an identical or somewhat modified form. Collocation indicates the relationship between words that often occur in the same environment. In use, each cohesive lexical device has a substantial and different function. By using lexical cohesion, the sentences relate to each other, making them enjoyable to read.